Erasmus experience between the University of Cadiz (Spain) and the University of Algarve (Portugal) - Laiz, Irene (2018)
A mobility program was carried out during the last two years between the Universities of Cadiz (Spain) and Algarve (Portugal) under the EU funded Erasmus+ Mobility for Teaching. The objective of the mobility was twofold: on one hand, it included the strengthening of the existing scientific cooperation between the University of Cadiz (home institution) and the University of Algarve (host institution) in the field of the Gulf of Cadiz Physical Oceanography; on the other hand, it pretended to improve the teaching quality, focusing on both the lecturers and the students. Both institutions have long ties of cooperation that have recently been intensified under the umbrella of the International Campus of Marine Excellence (CeiMar). Specific objectives oriented towards the lecturers included the exchange of teaching experiences among them as well as the comparison of teaching strategies and methodologies between the host and home institutions at the Master level in order to evaluate and enhance the best teaching practices with the aim of improving the students learning process. Specific objectives oriented towards the students included: (1) to provide local students that cannot afford studying a Master degree abroad with a foreign teacher in the discipline that will offer them different added expectations; (2) to teach students different subjects from those taught at the host institution, thus benefitting from new scientific knowledge and experiences. It must be pointed out that the subject taught by the home institution lecturer represents a competence lacking at the host institution, hence complementing the program of the discipline and providing an added value to the Master degree. Informal questionnaires carried out among students by the host institution revealed that they evaluated having a foreign teacher as a very positive experience. In terms of research, collaboration among both institutions is of great importance because they are both located within the same geographic region and hence, they share common interests. The mobility promoted finishing on-going collaborative publications as well as sharing new research experiences, data and knowledge, hence leading to an improvement of the Physical Oceanography state-of-the-art in the Gulf of Cadiz. In fact, two scientific papers on the Gulf of Cadiz circulation system and two on the storm climate along the Gulf of Cadiz and its relation with coastal hazards have been recently published as a direct result of the mobility program.